ARKTISKE FOLK SOM STATISTER OG AKTØRER PÅ DEN GLOBALE SCENE - Sejersen, Frank (Tidsskriftet Antropologi, 1996)
Frank Sejersen: Arctic people as by-standers and actors at the global stage For centuries, the indigenous peoples of the Arctic have been perceived as isolated from the rest of the world. The article argues that secluded Arctic communities do not exist and that Arctic peoples are integrated into numerous political, cultural and economic relations of a global extent. The pre-colonial inter-continental trade between Siberia and Alaska and the increased militarization the whole circumpolar region are but two examples. Throughout history, indigenous peoples of the Arctic have been players on the global stage. Today, this position has been strengthened because political work on this stage is imperative in order to secure the welfare and possibilities of local Arctic communities. To mention an example, Arctic peoples’ hunting activities have been under extreme pressure from the anti-harvesting movement. The anti-harvesting organizations run campaigns to ban hunting and stop the trade with products from whales, seals and furbearing animals. Thus, political and cultural processes far from the homeland of Arctic peoples, have consequences for the daily life of many Arctic families. The global stage has become an important comerstone in indigenous peoples’ strive to gain more control over their own future. The right to trade, development and self-determination are some of the rights they claim.